Evaluación de los indicadores productivos en pollos broiler con la adición de romero (Rosmarinus officinalis) en el balanceado como promotor de crecimiento, en el barrio San Antonio nº2, cantón Salcedo, provincia de Cotopaxi - Molina Vargas, Guadalupe Vanessa (2016)
This research performed in San Antonio No. 2 neighborhood, located in San Miguel parish, Salcedo city, to the south east side of Cotopaxi province, lasting 42 days. The aim research was to evaluate the productive indicators in broiler chickens with the addition of rosemary (Rosmarinus officinalis). Experimental methods, completely randomized design, with 100 chickens of Cobb 500 unsexed one day of age in four groups, with 25 chickens each was used, They were identified by groups according to the percentage of addition of rosemary : 1 % rosemary T1, 2 % rosemary T2, 3 % rosemary T3 on balanced and Witness T4....